The Influence of Price Discounts, Product Quality, and Reviews on Online Hijab Purchase Decisions - Salsabilla, Riezky; Hendrawan, Dimas (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study aims to analyze the extent to which discounts, product quality, and product reviews influence purchase decisions among consumers of Lafiye Official Shop on Shopee.co.id, particularly in Malang City. Employing a quantitative explanatory method, it examines causal relationships between these variables using data from 100 respondents selected through non-probability sampling with a purposive sampling technique. The data was gathered via validated and reliable research instruments, then analyzed using classical assumption tests and multiple linear regression in SPSS Version 25. This study finds that all three independent variables significantly influence consumer decisions to purchase Lafiye products sold on Shopee. These findings highlight the importance of managing digital consumer experiences in shaping purchasing behavior. The novelty lies in integrating three digital commerce variables in the hijab fashion segment, offering practical insights for online fashion marketing strategies.